Study on the pro-inflammatory mechanism of the HuD antibody in promoting M1 polarization and paraneoplastic neurological syndrome occurrence. Issue 4 (1st April 2022) - Yin, Liang; Yuan, Wen-Ling; Wu, Ke; Zhang, Li-Na; Li, Qian-Qian
ABSTRACT: Paraneoplastic neurological syndrome (PNS) is a nonmetastatic complication of malignant tumors that may lead to immune-mediated neuronal dysfunction or death. The occurrence of PNS results from the binding of anti-neuronal antibodies to neuronal cell surface antigens or intracellular antigens, which hinders the function of target proteins and promotes cell death. The aim of this study is to research the effect and immune mechanism of the neuronal ELAV-like protein (HuD antibody) on PNS-related syndrome. Neuronal cells were co-cultured with monocyte macrophages with or without HuD antibody. Next, we detected the apoptosis of neuronal cells by flow cytometry. Meantime, macrophage M1/M2 polarization factors and the secretion of inflammatory factors in the co-culture system were also detected by quantitative polymerase chain reaction (qPCR), Western blots and ELISA technologies. The results showed that after adding the HuD antibody in the co-culture system, the apoptosis level of the neuroma cells were significantly increased, and the apoptosis level were not significant changed when co-culture with monocytes without HuD antibody. In addition, the level of factors of M1 macrophages TNF-α, IL-12, TGF-β and IFN-γ increased, while the level of factors of M2 macrophages IL-10, IL-4, and Arg-1 decreased. The outcomes demonstrated that absorption of the HuD antibody by cerebellar neuronal cells could promote the proliferation of M1 macrophages and stimulates macrophages to secrete inflammatory factors, further damage the neuronal cells, eventually resulting in the occurrence of PNS. This finding provided a theoretical basis for the subsequent treatment and prevention of PNS. Graphical Abstract: uf0001